PRODUCER AND MARKETING GROUPS AND THEIR IMPACT ON FARMERS COMPETITIVE POSITION ON THE MARKET - Lemanowicz, Marzena (Acta Scientiarum Polonorum. Oeconomia, 2004)
In the article the conditions, which had an impact on development of agricultural producer groups in Poland, have been presented. There have been shown functions of these groups on the agricultural market. The main parts of the paper are results of the empirical researche that were carried out within 62 agricultural producer groups in Poland in 2001–2002. The results of researche have shown many advantages, which farmers got as a result of integrated activities. The advantages consist of finding new sales markets, products’ quality improvement, guarantee of delivery continuity and products’ preparations for sale. Moreover, in farms that belong to group, there have been noticed some changes, which contribute to the improvement of Polish agriculture competitiveness.